PHYTOCHEMICAL COMPOUNDS AND ANTIOXIDANT ACTIVITY OF YELLOW VELVETLEAF FRUIT (LIMNOCHARIS FLAVA) EXTRACT - BAEHAKI, ACE; LESTARI, SHANTI DWITA; SIREGAR, NORYATI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The purpose of this research was to observe the content of phytochemical compound and antioxidant activity of yellow velvetleaf fruit (Limnocharis flava) extract. Methods: Research consisted of several stages, including sampling, sample preparation, sample extraction, calculation of yield extract, phytochemical analysis (flavonoids, steroids, alkaloids, saponins, and triterpenoids), and antioxidant activity assessment using 2’,2’-diphenyl-1-picrylhydrazyl and iron-reducing power method. Results: The n-hexane and methanol extract contained flavonoids, saponins, and triterpenoids, while flavonoids and triterpenoids were detected on ethyl acetate extract. The IC50 of yellow velvetleaf extract with n-hexane, ethyl acetate, and methanol was 3321.67 ppm, 1439.24 ppm, and 96.0 ppm, respectively. The methanol extract had the highest iron-reducing power with the average absorbance of 0.588 followed by the ethyl acetate extract with the average absorbance of 0.195 and n-hexane extract had lowest with the average absorbance of 0.171. Conclusion: The best solvent to extract the yellow velvetleaf and have highest antioxidant activity was methanol solvent.